2013
DOI: 10.1055/s-0033-1339377
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient and Convenient Procedure for the One-Pot Synthesis of α-Aminophosphonates from Aryl Azides under Solvent-Free Conditions

Abstract: A novel and simple approach to the multicomponent one-pot reaction of aldehydes, diethyl phosphite, and azides to form α-aminophosphonates under solvent-free conditions at room temperature has been developed. In the presence of iodine and iron, aryl azides were, for the first time, used as substrates for the synthesis of α-aminophosphonates. The reactions were completed within 5 minutes to 12 hours and afforded the corresponding products in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…[7,8] In general, this threecomponent reaction may be carried out by the hydrophosphorylation of a Schiff base amine, which is catalyzed by an acid or base. [9][10][11][12] Oxidation of benzyl alcohols is a very important reaction in organic chemistry because it leads to the production of benzaldehyde which is used as precursors in the synthesis of organic compounds. Photooxidation of alcohols is of great interest for reasons such as a clean reaction and short duration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,8] In general, this threecomponent reaction may be carried out by the hydrophosphorylation of a Schiff base amine, which is catalyzed by an acid or base. [9][10][11][12] Oxidation of benzyl alcohols is a very important reaction in organic chemistry because it leads to the production of benzaldehyde which is used as precursors in the synthesis of organic compounds. Photooxidation of alcohols is of great interest for reasons such as a clean reaction and short duration.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that TBATB can catalyze the reaction of aldehyde with diethylphosphite and aniline in thermal condition (Entries 11-13). TBATB as a synthetic equivalent to bromine can be considered similar to iodine [12] in the second step. Surprisingly starting from alcohol is better than the corresponding aldehyde according to yields of reactions (Entries 11 and 12).…”
mentioning
confidence: 99%